O Consumo ritualístico do baile de debutantes - Estéban, Stephanie Duarte (2014)
This study examines the ritualistic consumption, called a debutante ball or as it is known in Brazil, the celebration of 15 years. The ritual is a type of social action in which there is the manipulation of cultural significance for purposes of collective and individual communication and categorization. Thus, the ritual is a powerful tool of meaning transfer from the consumer to the right. Symbolic artifacts, script, actors' role, audience (audience) and repetition: To be characterized as ritualistic experience, verification of certain elements is required. From these elements, the objective was to understand the debutante ball as ritual consumption, and analysis of the current meanings of the party. To develop this study was chosen qualitative methodology, motivated primarily by the need to investigate in depth the characterization of the debutante ball as ritualistic consumption from the identification of characterizing components of a ritual through oral history of six debutantes who were interviewed in Maringá-PR and São Sebastião do Paraíso, Minas Gerais. Data collection was based on three levels of interpretation of ritual symbols proposed by Victor Turner (1974). These are: (1) Exegetical, (2) Operational and (3) Positional. The first level was approached by oral history, documentary analysis by the second and third through participant observation. The results showed that the debutante ball is still recognized as a rite of passage, though its meaning was reframed due to changes in the society. The comparative approach between the dances of the two cities, it is concluded that there are more similarities than differences.